A STUDY TO EXPLORE SOCIO-ECONOMIC FACTORS IN THE DEVELOPMENT OF LOCAL COMMUNITIES - Haudi, .; Aseh, Khairi; Kenny, Kamal; Pathmathan, P. Ravindran (Archives of Business Research, 2020)
Economic growth in rural areas faces several challenges when comparing to urban regions. Limited employment opportunities and smaller profit from rural specific economic activities such as agriculture caused lower incomes to the local community. It is also very often that Agri-food products is undervaluation and not able to reach out outside market. This economic gaps between regions has resulted in several cases of outward migration flows of rural populations and land abandonment, which possibly brings major risk to the future of rural growth and sustainability. As reinforced by the needs to address the gaps and demands of the local community, therefore, this study was carried out to investigate the socio-economic demands and challenges of the local population in Temerloh, Pahang to recommend relevant assistance and interventions required. Findings from this study will provide important inputs that will suffice relevant literatures for the stakeholders to plan for a better socio-economic development in Malaysia. In general, the overall results of this study reveal the gaps faced by the community in the District of Temerloh in the context of social and economy. This study was carried out via a structured survey throughout the district involving 300 respondents and also complemented with a face-to-face interview carried out with key stakeholders.